A Class of Harmonic Univalent Functions Defined by Differential Operator and the Generalization - Aubdulnabi, Faten Fakher; Jassim, Kassim A. (Iraqi Journal of Science, 2020)
In this paper, a new class of harmonic univalent functions was defined by the differential operator. We obtained some geometric properties, such as the coefficient estimates, convex combination, extreme points, and convolution (Hadamard product), which are required